D.J. Ian Begg, Lost Worlds of Ancient and Modern Greece. Gilbert Bagnani: The Adventures of a Young Italo-Canadian Archaeologist in Greece, 1921-1924. - Struffolino, Stefano (Journal of Greek Archaeology, 2022)
D.J. Ian Begg, Lost Worlds of Ancient and Modern Greece. Gilbert Bagnani: The Adventures of a Young Italo-Canadian Archaeologist in Greece, 1921-1924. pp. xxxviii + 309, 14 ills, 5 maps, 1 tbl. Oxford: Archaeopress, 2020. ISBN 978-1-78969-452-9, hardcover £25.